2009
DOI: 10.1016/j.cmet.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

CXC Ligand 5 Is an Adipose-Tissue Derived Factor that Links Obesity to Insulin Resistance

Abstract: We show here high levels of expression and secretion of the chemokine CXCL5 in the macrophage fraction of white adipose tissue (WAT). Moreover, we find that CXCL5 is dramatically increased in serum of human obese compared to lean subjects. Conversely, CXCL5 concentration is decreased in obese subjects after a weight reduction program, or in obese non-insulin resistant, compared to insulin resistant obese subjects. Most importantly we demonstrate that treatment with recombinant CXCL5 blocks insulin-stimulated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
172
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(189 citation statements)
references
References 33 publications
14
172
2
1
Order By: Relevance
“…34 The alteration of MCP-1 levels mirrored the changes in the content of CD45 þ /14 þ cells, whereas CXCL5 already decreased after VLCD, as reported by Chavey et al 34 Nevertheless, we did not find correlation between these chemokines and ATM content. The lack of relation may be explained by the fact that these molecules are secreted into the circulation by various cells in different tissues.…”
Section: Discussioncontrasting
confidence: 49%
“…34 The alteration of MCP-1 levels mirrored the changes in the content of CD45 þ /14 þ cells, whereas CXCL5 already decreased after VLCD, as reported by Chavey et al 34 Nevertheless, we did not find correlation between these chemokines and ATM content. The lack of relation may be explained by the fact that these molecules are secreted into the circulation by various cells in different tissues.…”
Section: Discussioncontrasting
confidence: 49%
“…Previous studies have shown that MCP-1 triggers this macrophage infiltration and that modulation of the MCP-1/CCR2 signaling by genetic disruption or treatment with an inhibitory molecule can ameliorate obesity-induced insulin resistance (5,6,23,24,28). Other chemokines have recently been suggested to also promote macrophage infiltration in obesity (8,29,30). Receptors for these chemokines, including CCR2, are GPCRs, of which PI3Kγ lies downstream and mediates the signal to promote cell movement in response to chemokine stimulation (10,11,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that obesity induces hematopoietic cell infiltration into adipose tissue, which in turn enhances adipose tissue inflammation and the secretion of proinflammatory adipokines, leading to systemic insulin resistance (3)(4)(5)(6)(7)(8). Inhibition of macrophage infiltration into adipose tissue could be considered a therapeutic strategy on the basis of the accumulated evidence of obesity-related metabolic disorders.…”
mentioning
confidence: 99%
“…However, very recent data strongly suggest that SOCS-2 is a key actor in modulating insulin signal in muscle. Indeed, it has been shown that chemokine CXC ligand-5 induces insulin resistance mainly by inhibiting insulin signalling in muscle, which may be driven by SOCS-2 production [36]. Moreover, a given SOCS protein appears to promote the proteasomal degradation of other SOCS proteins [37].…”
Section: Discussionmentioning
confidence: 99%